Analisis Kesalahan Berbahasa Teks Editorial pada Modul Ajar Bahasa Indonesia Karya Foy Ario, M.Pd. sebagai Kelayakan Bahan Ajar Membaca Kritis Siswa Kelas XII - Hilda Af’idatussofa; Rani Diah Setyaningsih; Atiya Najal Aufa; Hikmatul Amelia; Yolanda Prety Nazhifa Hanun; Asep Purwo Yudi Utomo; Samuel B.T. Simorangkir (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Language is an efficient way to express ideas, emotions, and feelings to communicate a concept through verbal and non-verbal means. Comprehensive learning of language skills is intended to promote emotional, social, and intellectual development, and is useful for filtering important information. The purpose of this study is to determine the location of language errors from the module used, namely in the Indonesian teaching module by Foy Ario, M.Pd, as the feasibility of teaching materials for critical reading for class XII students, so that it can be used as a revision in the future to obtain a quality module, both in terms of the information conveyed and the language used. This research method uses a descriptive qualitative approach as well as a syntactic theoretical approach and analyzes data through data collection, data presentation, data reduction, and conclusion drawing. The results obtained show that the writing of editorial text contained in the Indonesian language teaching module Class XII SMA by Foy Ario is found to use diction that is not by the rules. This is based on standardized word errors, conjunction errors, punctuation errors, word beheading errors, and errors in the accuracy of word usage and effective sentences. The research can be useful as a reference for understanding language identification in scientific papers.